Funciones Administrativas y su Influencia al Proceso de Producción en la Empresa Jorge Pintado Confecciones - Villegas Ponce, Genesis Eloysa (2017)
The following document contains theoretical fragments of how administrative functions are developed, which needs to know all good managers and the optimal functioning of family businesses, in order to generate profits and provide products of excellent quality to the market segment that is focused